The usefulness and wellbeing of Tofacitinib in the treatment of Alopecia Areata - Khondker, Lubna; Sultana, Abida; Khan, Md Shirajul Islam (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Treatment options for alopecia areata are limited and often inadequate but the use of an oral Janus kinase inhibitor such as Tofacitinib is considered promising treatment of alopecia areata. Objective: To evaluate the usefulness and wellbeing of Tofacitinib in the treatment of alopecia areata. Materials and Methods: This clinical trial was conducted at the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during July 2018 to December 2019. A total of 45 patients with patchy alopecia areata (at least> 50% scalp involvement), in the form of alopecia totalis and alopecia universalis were treated with Tofacitinib at 5mg twice daily for 6 months. Clinical testing was performed on the basis of the Severity of Alopecia Tool Score (SALT). Results: The average age of the patients was 33.00 ± 13.1 years. For them 40.0% of patients' age was less than 20 years. In addition, 26 (57.8%) were infected with patchy alopecia areata with> 50% of scalp involvement, 11 (24.4%) had Alopeciatotalis and 8 (17.8%) Alopecia universalis. The average duration of illness was 1.2 ± 0.6 years. Clinical follow-up revealed that among the 26 patients with patchy alopecia areata with> 50% of scalp involvement, 15.4% had a gradual growth and 84.6% re-growth of full hair. Of the 11 patients with Alopecia totalis, 27.3% had a partial rejuvenation and 72.7% re-growth of hair and among the 8 patients with Alopecia universalis, 37.5% had a gradual increase and 62.5% had a recurrence for perfect hair. In terms of well-being, 34 patients (75.6%) did not experience side effects but 11 patients (24.4%) experienced side effects such as 18.2% nausea, 72.7% headache and 9.1% had high infection of respiratory tract (URTI). Conclusion: The treatment of alopecia areata by tofacitinib, Janus kinase inhibitors are effective, safe and sound in the treatment of alopecia areata. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 43-47